2000
DOI: 10.15760/etd.2654
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Fungal Communities of the Dioicous Moss Ceratodon purpureus

Abstract: Mosses display a number of hallmark life history traits that influence their ecology at the population and community level. The long lived separation of sexes observed in the haploid gametophyte (dioicy) is one such feature of particular importance, as it is observed in the majority of bryophytes and creates intraspecific specialization of male and female individuals.The prevalence of sexually dimorphic mosses raises the possibility of sex-specific interactions with fungi as observed in some vascular plants. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 120 publications
1
8
0
Order By: Relevance
“…Additionally, our results suggest that natural populations of C. purpureus which lack commensal arthropods may be sperm-limited, a result previously reported in other moss species [52]. Currently, it is unclear what reward, if any, springtails gain from the behavior, although a moss could provide food sources such as secreted sugars and fatty acids [25,53,54], bacteria or fungi [55], or the moss itself [56].…”
Section: Discussionsupporting
confidence: 58%
“…Additionally, our results suggest that natural populations of C. purpureus which lack commensal arthropods may be sperm-limited, a result previously reported in other moss species [52]. Currently, it is unclear what reward, if any, springtails gain from the behavior, although a moss could provide food sources such as secreted sugars and fatty acids [25,53,54], bacteria or fungi [55], or the moss itself [56].…”
Section: Discussionsupporting
confidence: 58%
“…In mosses, thicker and larger leaves may allow females greater protection against fungal pathogens, which occur at high densities in moss communities (Davey and Currah, 2006;Davey et al, 2013). Indeed, males from these same study populations, with thinner leaves, were recently found to have higher fungal biomass and richness than females (Balkan, 2016). In fact, if the higher photochemical values in females allow for greater overall net assimilation, this could provide the resources needed for fungal chemical defences and/or volatile compounds that have been hypothesized as contributing to an early 'plant pollinator'-like syndrome in C. purpureus (Cronberg et al, 2006;Cronberg, 2012;Rosenstiel et al, 2012).…”
Section: Sex-specific Differencesmentioning
confidence: 85%
“…However, in bryophytes, we know little about the breadth of between-sex diversity in morphological traits (Shaw and Beer, 1999;McLetchie and Puterbaugh, 2000;Horsley et al, 2011) or physiological traits (Stark et al, 2005;McLetchie and Stark, 2006;Groen et al, 2010), and comparatively little emphasis has been placed on understanding the underlying sex-specific physiological differences in dioecious mosses at a finer scale and their contributions to sexual dimorphisms (Stark et al, 2009). Developing this sex-specific framework is also important for understanding how moss-dominated ecosystems (the bryosphere), which occur on every continent and dominate major portions of the earth's surface, shape the function and diversity of heterotrophic communities (Lindo and Gonzalez, 2010;Balkan, 2016) and consequently nutrient cycling (Cornelissen et al, 2007;Turetsky et al, 2012;Delgado-Baquerizo et al, 2016) in ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Other local influences exerted by moss emitted BVOC's may include sex-specific volatile compounds that influence microarthropods mediated fertilization in mosses(Rosenstiel et al 2012). Further, there are sex-specific fungal communities that affect their ecology(Sharkey et al 2001;Devika et al 2012;Kandi et al 2015, Balkan 2016.Mosses can influence nearby atmospheric process by emitting isoprene which is reduced by hydroxyl radical (OH) into water droplet nucleation. Secondary Organic Aerosol (SOA) acts as a local form of cloud or fog seeding allowing plants to exert influence on the atmospheric hydrological conditions of its local microclimate.…”
mentioning
confidence: 99%